Virtual Singapura - Cheong, Wei Lun. (2009)
The recent years have seen a popular rise in the gaming industry, especially in the area of Massively Multiplayer Online Role Playing Games (MMORPGs). Millions of people all around the world now call home to a particular MMORPG of their choice. This is especially for the younger generation who play such MMORPGs and they are used to the graphical experience, content and social interaction provided by many of these games. As such, many education sectors have embraced the use of such MMORPGs as a means to create an environment where students can learn and have fun at the same time. This project proposes the use of a commercial 3D game engine and several models from a previous 3D application to develop a Virtual Singapura World. This enables students to experience ancient Singapore in a 3D environment, interact with Non-Player characters (NPCs) and their fellow students and play some mini games while learning about the history and culture. This also enables teachers to integrate the required secondary school history curriculum into the world itself, creating scenarios and resources where students can also learn about the history of Singapore whilst having fun.